2011
DOI: 10.1038/mt.2011.30
|View full text |Cite
|
Sign up to set email alerts
|

Secreted Antiviral Entry Inhibitory (SAVE) Peptides for Gene Therapy of HIV Infection

Abstract: Gene therapeutic strategies for human immunodeficiency virus type 1 (HIV-1) infection could potentially overcome the limitations of standard antiretroviral drug therapy (ART). However, in none of the clinical gene therapy trials published to date, therapeutic levels of genetic protection have been achieved in the target cell population for HIV-1. To improve systemic antiviral efficacy, C peptides, which are efficient inhibitors of HIV-1 entry, were engineered for high-level secretion by genetically modified ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 46 publications
4
23
0
Order By: Relevance
“…VRX496-T did not selectively expand in the presence of viremia, confirming mathematical modeling 16,35 and indicating that VRX496, as expected, does not protect transduced cells once they are infected. Alternative approaches may be needed, such as combination with a more potent genetic antiviral to drive selective outgrowth of cells during viremia 1,[36][37][38] or preinfusion conditioning regimens to promote homeostatic proliferation of the infused cells to enhance engraftment 39 and facilitate durable efficacy. …”
Section: Discussionmentioning
confidence: 99%
“…VRX496-T did not selectively expand in the presence of viremia, confirming mathematical modeling 16,35 and indicating that VRX496, as expected, does not protect transduced cells once they are infected. Alternative approaches may be needed, such as combination with a more potent genetic antiviral to drive selective outgrowth of cells during viremia 1,[36][37][38] or preinfusion conditioning regimens to promote homeostatic proliferation of the infused cells to enhance engraftment 39 and facilitate durable efficacy. …”
Section: Discussionmentioning
confidence: 99%
“…The HIV-1 HxB2 -derived peptide C46 ( Fig. 1), which has already been used in preclinical and clinical gene therapy studies (15,(35)(36)(37), was used as a control peptide in this study.…”
Section: Substitution Of Primary Anchor Amino Acids Reduced the Numbementioning
confidence: 99%
“…Recently, promising results were obtained with the fusion inhibitor C46 (FI C46 ), which is a peptide derived from the HIV envelope (Env) glycoprotein gp41 that prevents membrane fusion. 32 Secreted neutralizing antibodies were also tested, 33,34 but their neutralization breadth was limited. 35 Clinical trials using passive transfer of these antibodies have shown emergence of resistant viruses.…”
Section: Introductionmentioning
confidence: 99%